Lipofibromatous hamartoma of sciatic nerve: A case report. (September 2022) - Khadka, Sulochana; Adhikari, Prashant; Regmi, Pradeep Raj; Timilsina, Bibek; Thapa, Anupam Singh; Panta, Bhaskar Raj; Bhandari, Sandeep
Abstract: Introduction: Lipofibromatous hamartoma of the nerve is the fibro-fatty overgrowth within the nerve. Most commonly they occur in the median nerve, ulnar nerves, and a few other nerves but the involvement of the sciatic nerve is very rare. The fibro-fatty infiltration causes palpable neurogenic mass and clinically presents lump, moderate numbness, tingling sensation, and pain in its territory. Magnetic resonance imaging is the gold standard for diagnosis. Case presentation: We present a case of a 65 years old female, who presented to OPD with a tingling sensation which progressed to pain in the gluteal region and was associated with a tender swelling. MRI showed a giant space-occupying lesion in the sciatic nerve course. The mass was excised and then sent to the histopathological examination which designated the mass as lipofibromatous hamartoma. Discussion: Unless debilitating, lipomatosis of the nerve doesn't require any intervention as it is a benign condition. Lipofibromatous hamartoma is attributed to the accumulation of fatty and fibrous tissue in the epineurium. Diffusion-weighted imaging in association with conventional magnetic resonance imaging has increased diagnostic yield. The lesion was iso-intense to the subcutaneous fat and there were fine fibrillar appearances inside of it. Simple mass excision was performed on our patient without complications. Conclusion: Lipofibromatous hamartoma of the nerve are rare soft tissue tumors of nerves and sciatic nerve involvement is even rarer. Correct and careful interpretation of the MRI findings can lead to diagnosis with ease and help prevent unnecessary biopsies. Highlights: Fibrolipomatous hamartoma of the sciatic nerve is a rare disease which may be asymptomatic or may present with palpable tender swelling and tingling sensation in the territory of the nerve. High soft tissue resolution MRI is the gold standard for diagnosis and helps prevent unnecessary nerve biopsies. Debulking, internal or external neurolysis or radical excision with or without fascicular grafts are various mode of intervention in case of fibrolipomatous hamartoma.